The Effect of System Quality and Information Quality of The Student Academic Portal on User Satisfaction in Accounting Students - Sitorus, Atikah; Manao, Marcella; Sari, Nurmala; Ramadhani, Suci; Fachruddin, Wan (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2025)
This study aims to analyze the effect of system quality and information quality of the academic portal on user satisfaction among accounting students at Universitas Pembangunan Panca Budi. The method used in this research is a quantitative approach with descriptive and analytical design. Data was collected through an online questionnaire distributed to 323 students, with the sample determined using the Slovin formula, resulting in 76 respondents. Data analysis was carried out using multiple linear regression with the help of SPSS software version 21. The results showed that there was a significant positive influence between system quality and information quality on user satisfaction. Students expect improvements in portal accessibility, especially when filling out KRS, as well as reducing distractions such as annoying advertisements. This study concludes that improving the quality of academic portal systems and information can increase user satisfaction, which in turn supports a more effective teaching and learning process.